Gambaran Anemia pada Pasien Anak Pasca Operasi yang Dirawat di PICU RSUD Arifin Achmad Periode 2018-2020 - Pasaribu, Hotber; Faradina, Adinda (Jurnal Ilmu Kedokteran, 2024)
Surgery is an invasive treatment that consists of major and minor surgery. Post-major surgery patients require comprehensive intensive care, including checking hemoglobin levels to detect anemia. Post-operative anemia can occur in 80-90% of patients undergoing major surgery. The purpose of this study was to describe anemia in post-operative pediatric patients treated in PICU Arifin Achmad Hospital for the 2018-2020 period. The design of this study is descriptive cross sectional with retrospective approach using medical record of pediatrics with 169 samples. The results showed that the majority of preoperative pediatrics patients were not anemic (73,4%) and were not given blood transfusions (76,3%). Postoperative pediatric patients dominantly anemic (53,8%). The majority of postoperative anemia incidence occurred in the age group 6-59 months (54,9%), male gender (57,1%), and location of abdominal surgery (71,4%). The type of anemia based on erythrocyte index in postoperative was microcytic hypochromic (61,5%). These findings highlight the importance of monitoring anemia in pediatric patients post-surgery to improve clinical outcomes and reduce complications.